Speech Prosody 2020 2020
DOI: 10.21437/speechprosody.2020-116
|View full text |Cite
|
Sign up to set email alerts
|

Speech rhythm in multiethnolectal Zurich German

Abstract: Multiethnolects have been observed in (Western) Europe for about 30 years, also in Zurichthe biggest city in German-speaking Switzerland, characterized by ethnic and linguistic diversity. Speech rhythm appears to be a salient feature of several European multiethnolects and has been described as a 'staccato' rhythm. However, a sociophonetic investigation of rhythm in Swiss German multiethnolects is lacking so far. To investigate rhythmic characteristics of multiethnolectal Zurich German, we recorded read speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…On the segmental level, fricative duration in word-initial position correlates significantly with mean rating score (Morand et al, 2019b). On the suprasegmental level, we found significant correlations between mean rating scores and vowel variability measurements, in particular the Normalized Pairwise Variability Index nPVI (Grabe & Low, 2002) as well as syllable rate (Morand et al, 2020). The use of less vowel reduction in unstressed syllables in multiethnolectal Zurich German leads to the impression of a 'staccato' rhythm of this variety.…”
Section: From Perception To Productionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the segmental level, fricative duration in word-initial position correlates significantly with mean rating score (Morand et al, 2019b). On the suprasegmental level, we found significant correlations between mean rating scores and vowel variability measurements, in particular the Normalized Pairwise Variability Index nPVI (Grabe & Low, 2002) as well as syllable rate (Morand et al, 2020). The use of less vowel reduction in unstressed syllables in multiethnolectal Zurich German leads to the impression of a 'staccato' rhythm of this variety.…”
Section: From Perception To Productionmentioning
confidence: 75%
“…How the pronunciation and lexical choices of adolescent speech are perceived and socially interpreted is one of the issues investigated in our research project. In the present study, instead, we do not focus on the production of specific linguistic features (see, however, Morand et , 2019b;Morand et al, 2020;Morand et al, accepted); rather, our aim is to discuss general methodological aspects involved in research on sociolinguistic per ception, such as the labels to be used in rating experiments on speech styles and the discrete or continuous nature of cognitive representations related to multiethnolectal speech.…”
Section: Typical Features Of Multiethnolectal Zurich Germanmentioning
confidence: 99%
“…In a previous study on read speech, we found slower syllable rates in speakers of rather multiethnolectal Zurich German (MEZ) compared to speakers of rather traditional Zurich German [24]. Based on a rating experiment, adolescents could be placed on a perceptual continuum between multiethnolectal and traditional Zurich German [25].…”
Section: Introductionmentioning
confidence: 78%
“…This characteristic of MEZ is taken up by a comedian to caricature the multiethnolectal way of speaking in a very exaggerated way (11.24 seg/sec [32]). Subsequently, our first quantitative analysis of read speech from 48 adolescents recorded in Zurich [24] revealed significant negative correlations between the perceptual ratings assigned to multiethnolectal speakers and their syllable rate as well as their vowel duration variability. Thus, speakers who were perceived as speaking rather MEZ showed slower syllable rates and less vowel duration variability.…”
Section: Multiethnolectal Zurich Germanmentioning
confidence: 99%